MP19: Comparison of the psychometric properties of the VAS, FPS-R and CAS in the pediatric emergency department. (15th May 2017) - Ali, S.; Le May, S.; Plint, A.; Ballard, A.; Khadra, C.; Mâsse, B.; Auclair, M.; Neto, G.; Drendel, A.L.; Villeneuve, E.; Parent, S.; McGrath, P.; et al.
Abstract : Introduction: Appropriate pain management relies on the use of valid, reliable and age-appropriate tools that are validated in the setting in which they are intended to be used. The aim of the study was to assess the psychometric properties of pain scales commonly used in children presenting to the pediatric emergency department (PED) with an acute musculoskeletal injury.Methods: Convergent validity was assessed by determining the Spearman's correlations and the agreement using the Bland-Altman method between the Visual Analogue Scale (VAS), Faces Pain Scale-Revised (FPS-R) and Color Analogue Scale (CAS). Responsiveness to change was determined by performing the Wilcoxon signed-rank test between the pre-post analgesia mean scores. Reliability of the scales was estimated using relative (Spearman's correlation, Intraclass Correlation Coefficient) and absolute indices (Coefficient of Reliability).Results: A total of 495 participants was included in the analyses. Mean age was 11.9 ±2.7 years and participants were mainly boys (55.3%). Correlation between each pair of scales was 0.79 (VAS/FPS-R), 0.92 (VAS/CAS) and 0.81 (CAS/FPS-R). Limits of agreement (80%CI) were -2.71 to 1.27 (VAS/FPS-R), -1.13 to 1.15 (VAS/CAS) and -1.45 to 2.61 (CAS/FPS-R). Responsiveness to change was demonstrated by significant differences in mean pain scores, among the three scales, between pre- and post-medication administration (p<0.0001). ICC and CR estimates suggested acceptable reliability for the three scales at 0.79 and ±1.49 for VAS, 0.82 and ±1.35 for CAS, and 0.76 and ±1.84 for FPS-R.Conclusion: The scales demonstrated good psychometric properties with a large sample of children with acute pain in the PED. The VAS and CAS showed a stronger convergent validity, while FPS-R was not in agreement with the other scales. Clinically, VAS and CAS scales can be used interchangeably to assess pain intensity of children with acute pain.